Networks in the Field of Tourette Syndrome - Kleimaker, Alexander; Kleimaker, Maximilian; Behm, Amelie; Weissbach, Anne; Bäumer, Tobias; Beste, Christian; Roessner, Veit; Münchau, Alexander (Frontiers in Neurology, 2021)
Gilles de la Tourette syndrome is a neuropsychiatric neurodevelopmental disorder with the cardinal clinical features of motor and phonic tics. Clinical phenomenology can be complex since, besides tics, there are other features including premonitory urges preceding tics, pali-, echo- and coprophenomena, hypersensitivity to external stimuli, and symptom dependency on stress, attention, and other less well-defined factors. Also, the rate of co-morbidities, particularly attention deficit hyperactivity disorder and obsessive-compulsive disorders is high. Mirroring the complexities of the clinical course and phenomenology, pathophysiological findings are very diverse and etiology is disputed. It has become clear though that abnormalities in the basal ganglia and their connections with cortical areas are key for the understanding of the pathophysiology and as regards etiology genetic factors are crucial. Against this background, both adequate clinical management of TS and TS-related research require multi-disciplinary preferably international cooperation in larger groups or networks to address the multiple facets of this disorder and yield valid and useful data. In particular, large numbers of patients are needed for brain imaging and genetic studies. To meet these requirements, a number of networks and groups in the field of TS have developed over the years creating an efficient, lively, and supportive international research community. In this review, we will provide an overview of these groups and networks.